Laying the foundation for successful school leadership - Burkhauser, Susan; Gates, Susan M., 1968-; Hamilton, Laura S.; Li, Jennifer; Pierson, Ashley (RAND, 2013)
Principals can influence student achievement in a number of ways--monitoring instruction; evaluating teachers; hiring, developing, and retaining school staff; maintaining student discipline; managing the school budget; establishing a school culture; and engaging with the community. While principals' skills in these areas are important, skills alone are not enough to ensure that they will be effective school leaders. This is because school and district contexts--which include school and district characteristics, practices, and policies--set the stage for principals' performance and strongly influence their effectiveness. In this report, RAND researchers provide guidance to state and district decisionmakers and others who manage school systems, focusing on four areas that research has identified as particularly influential in supporting principal effectiveness: placement in the school, evaluation, autonomy, and resources. We highlight how actions in these areas can create conditions in the school and district that foster principal success.